What drives satisfaction? Assessing field training in bachelor’s social work programs - Ghaboush, Reham Abu; Atieh, Nesreen Nabil; Tarawneh, Haya Hussein; Alhur, Mohammad; Anabtawi, Manal Fathi (International Journal of Innovative Research and Scientific Studies, 2025)
Social work is a humanitarian profession that intersects with a variety of fields. It focuses on supporting individuals through the effective utilization of resources and the recognition of their potential. To practice effectively, social workers require substantial professional development, which includes extensive field training. This training is crucial as it allows them to apply theoretical knowledge in real-world settings while acquiring essential skills. Governments increasingly acknowledge the importance of field training in educating social workers. This study presents a unique contribution to the field of social work education by evaluating the impact of field training quality on student satisfaction among bachelor’s students at the University of Jordan. To achieve this, a quantitative methodology was employed, surveying 137 bachelor students during the academic year of 2023/2024. The data were analyzed using Structural Equation Modeling (SEM). The findings highlight that factors such as assurance, tangibles, and responsiveness significantly influence student satisfaction with the field training program. Conversely, reliability and empathy did not significantly impact, suggesting a disconnect between what students expect and what is delivered. The structural model accounts for approximately one-third of the variation in satisfaction, underscoring the necessity to enhance service quality factors to improve the effectiveness of field training programs.